Peran Perempuan Hindu Dalam Pelaksanaan Upacara Ngaben (Studi di Dusun Wana Sari Desa Swastika Buana Kecamatan Seputih Banyak Kabupaten Lampung Tengah) - Wayan Sukarlinawati (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2023)
In Balinese society, it has been proven that many women are capable of carrying out tasks as befits men, such as being a sulinggih, pampangku (jan bangul), but women are generally reluctant to choose this opportunity to become the field they are engaged in. Scriptures or guidelines in ejection are often used as an excuse to perpetuate injustice regarding the provisions that must be obeyed by women in religious activities/prayers. Women play an important role in being involved in religious ceremonies and other Yajna activities. One of the important roles of women is their involvement in the Pitra Yajna ceremony, namely the Ngaben ceremony. The purpose of this study is to analyze the role of women in carrying out the cremation ceremony in Wana Sari Hamlet, Swastika Buana Village, Seputih Banyak District, Central Lampung Regency and to analyze the shape of the role of women in the Ngaben ceremony in Wana Sari Hamlet, Swastika Buana Village, Seputih Banyak District, Central Lampung Regency. The method used in this study is a qualitative research method related to field research which is usually research related to the social sciences. The results of the study are that women have a social role in society and secondly, the role of women is to strengthen a sense of solidarity in the effort to transform religious values and the division of responsibilities for the implementation and development of religious rituals, especially at the Ngaben ceremony, is sustainable. The role that women have in carrying out the Ngaben ceremony is that the women specifically make Banten Upakara, while the men handle other equipment that requires more manpower, such as making bade and others. The rights of Hindu women in the Ngaben ceremony greatly determine the Atman and all of their ancestors in order to achieve perfection and happiness in God's realm.